I do not want to set my own price! Indirect effects of emotions and moderation effects of skepticism explain reduced use intentions towards participative pricing models - Wittstock-Lang, Regina; Bekk, Magdalena; Spörrle, Matthias (PloS one, 2023)
Participative pricing models (i.e., auction, reverse auction, pay-what-you-want) have grown in importance compared to classical, non-participative pricing models (i.e., fixed price, discount). This study examined (1) relative use intentions regarding different (non-) participative pricing models, (2) the emotional responses triggered by the pricing models and influencing consumers’ use intentions, and (3) the moderating role of individual skepticism in this context. A between-subjects experiment ( N = 505) with five groups, manipulating participative (auction, reverse auction, and pay-what-you-want) and non-participative (fixed price and discount) pricing models, detected reduced use intentions towards participative compared to non-participative pricing models. Even though participative pricing models induced higher levels of positive as well as negative emotions, the effects via positive emotions (promoting use intentions) were weaker than the effects via negative emotions (mitigating use intentions). Skepticism towards participative pricing models enhanced negative emotions and decreased positive emotions. Practical applications should rely on enhancing positive emotions while simultaneously reducing negative emotions, as they exert independent effects. Skepticism of potential users should be mitigated in the early stages of the customer relationship, e.g., via trustworthiness triggers.